A novel P2RX2 mutation in an Italian family affected by autosomal dominant nonsyndromic hearing loss. - Faletra, Flavio; Girotto, Giorgia; d'Adamo, Adamo Pio; Vozzi, Diego; Morgan, Anna; Gasparini, Paolo (Gene, 2014)
Hereditary hearing loss (HHL) is a common disorder accounting for at least 60% of prelingual deafness. It is characterized by a large genetic heterogeneity, and despite the presence of a major gene, still there is a need to search for new causative mutations/genes. Very recently, a mutation within ATP-gated P2X(2) receptor (ligand-gated ion channel, purinergic receptor 2) gene (P2RX2) at DNFA41 locus has been reported leading to a bilateral and symmetrical sensorineural non-syndromic autosomal dominant HHL in two Chinese families. We performed a linkage analysis in a large Italian family with a dominant pattern of inheritance showing a significant 3.31 LOD score in a 2Mb region overlapping with the DNFA41 locus. Molecular analyses of P2RX2 identified a novel missense mutation (p.Gly353Arg) affecting a residue highly conserved across species. Visual inspection of the protein structure as obtained from comparative modeling suggests that substitution of the small glycine residue with a charged bulky residue such as an arginine that is close to the 'neck' of the region responsible for ion channel gating should have a high energetic cost and should lead to a severely destabilization of the fold. The identification of a second most likely causative mutation in P2RX2 gene further supports the possible role of this gene in causing autosomal dominant HHL.
Keywords: Amino Acid Sequence; Deafness; European Continental Ancestry Group; Female; Genotype; Hearing Loss, Sensorineural; Humans; Italy; Male; Molecular Sequence Data; Mutation, Missense; Pedigree; Receptors, Purinergic P2X2